Pengaruh Lingkungan Pengendapan terhadap Sebaran dan Kualitas Lapisan Batubara di Desa Kalasari, Papua Barat Daya - Yosiyan Daniel Sinaga; Aang Panji Permana; Muh Kasim (Journal of Applied Geoscience and Engineering, 2025)
This study was conducted in Kalasari Village, Salawati District, Sorong Regency, Southwest Papua, within the Contract of Work area of PT Megapura Prima Industri. The research integrated field geological observations, detailed lithological and outcrop descriptions, drill core logging and correlation, and laboratory proximate analysis to characterize coal occurrence and quality. Stratigraphic analysis indicates that the study area is composed of two principal lithological units: the Sele Claystone Unit, deposited in backswamp to swamp environments, and the Sele Sandstone Unit, representing floodplain facies. Borehole correlation reveals coal seam thicknesses ranging from 0.3 to 1.82 m, with a general westward thickening trend, reflecting microtopographic variation and peat stability during deposition. The roof and floor of the coal seams are dominantly claystone or clayey sandstone, indicating overbank flood sedimentation that facilitated peat preservation. Proximate analysis shows that the coal is low rank, characterized by calorific values of 3220–3619 kcal/kg (adb), low ash content (1.7–3.8%), very low sulfur content (0.2%), and high total moisture (32–37%). These characteristics are typical of freshwater swamp–backswamp facies within an upper delta plain depositional environment with limited clastic input. The relatively thin overburden further constrained coalification, resulting in low calorific values. Overall, the results demonstrate that coal distribution, seam thickness, and coal quality in the study area are strongly controlled by upper delta plain depositional dynamics, particularly swamp and backswamp facies that governed peat accumulation and preservation.